Hubungan Pemanfaatan Artificial Intelligence (AI) dengan Kemampuan Menulis Teks Puisi - Marsiana Yuni; Al Ashadi Alimin; Mesterianti Hartati (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
The development of Artificial Intelligence (AI), particularly Large Language Models such as ChatGPT, has changed the paradigm of creative writing learning in secondary schools. However, empirical evidence regarding the relationship between the intensity of this technology utilization and the quality of students' literary works is still limited. This study aims to examine the relationship between AI utilization and the poetry writing skills of grade XI students at Karya Budi Putussibau Senior High School. The method used was a quantitative correlational method with a sample of N = 27 students selected through a random sampling technique. Data were collected using an AI utilization questionnaire (30 valid and reliable statements, (α= 0.975) and a poetry writing test assessed with an analytical rubric. The results of descriptive statistical analysis showed that the level of AI utilization was in the high category (M = 3.70) and students' poetry writing skills were in the good category (M = 78.41). The Pearson Product Moment correlation test showed a very strong and significant positive relationship between the two variables (r = 0.978; p < 0.01). These findings confirm that proper AI integration acts as a creative catalyst that helps students explore diction and imagery structure in the poetry writing process.